Figure 7 from: Sikes D, Stockbridge J (2013) Description of Caurinus tlagu, new species, from Prince of Wales Island, Alaska (Mecoptera, Boreidae, Caurininae). ZooKeys 316: 35-53. https://doi.org/10.3897/zookeys.316.5400 - Sikes, Derek; Stockbridge, Jill (Zenodo, 2013)
Figure 7 - Base of Caurinus antenna showing sensilla on antenomeres 4, 5, and 6. A female Caurinus dectes (UAM:Ento:230088), B female Caurinus tlagu (UAM:Ento:203237); sen = sensilla, scale bars = 20 µm.